The Role of Teacher Professional Learning in Indigenous Language Reclamation - Tulloch, Shelley; Fontaine, Lorena; Souter, Heather (Minorités linguistiques et société / Linguistic Minorities and Society, 2025)
Universities must support Indigenous language reclamation; this includes training Indigenous language teachers. Though specialized programs are offered across Canada, they have not provided Indigenous language teachers with the training or support they need to teach languages in ways that will create new speakers, expand language use, and combat the erasure and silencing of Indigenous languages. This article triangulates findings from an environmental scan on professional learning for Indigenous language teachers, a literature review on good practices in Indigenous language teacher training and Indigenous language pedagogies, and the self-study (Pinnegar & Hamilton, 2009) of faculty members and an Indigenous organization lead involved in the development and delivery of the University of Winnipeg’s Indigenous Languages programs. We explore evidence of the need for Indigenous language teacher training; examples of relevant programs; as well as opportunities, challenges and promising practices in Indigenous language teacher training, and implications for language revitalization.